Please help me.

If *x* = \(2 + \sqrt[3]{2} + \sqrt[3]{2^2}\), Then \(x^3 - 6x^2 + 6x\) = ?

Please help me.

If *x* = \(2 + \sqrt[3]{2} + \sqrt[3]{2^2}\), Then \(x^3 - 6x^2 + 6x\) = ?

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

## Comments

Sort by:

TopNewestTake 2 on LHS and cube on both the sides

\(\displaystyle (x-2)^3 = 2(1 + 2^{\frac{1}{3}})^3\)

Simplifing

\(\displaystyle x^3 -6x^2 + 12x - 8 = 6(1 + 2^{\frac{1}{3}} + 2^{\frac{2}{3}})\)

Rearranging (formation of x on RHS)

\(\displaystyle x^3 -6x^2 + 12x -8 = 6x -6\)

\(\displaystyle x^3 - 6x^2 + 6x = 2\) – Krishna Sharma · 2 years, 1 month ago

Log in to reply

– Swapnil Das · 2 years, 1 month ago

Can U please recommend me some books for trigonometry?Log in to reply

– Krishna Sharma · 2 years, 1 month ago

I never read any Trigonometry books but I am sure Omkar kulkarni can help you out(I am unable to tag him right now)Log in to reply

– Swapnil Das · 2 years, 1 month ago

Thanks for suggestion!Log in to reply

– Swapnil Das · 2 years, 1 month ago

Thank You. You were really helpful!Log in to reply

x=2 – Jacob Johanssen · 2 years ago

Log in to reply